2020
DOI: 10.1016/j.isatra.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Fault detection for planetary gearbox based on an enhanced average filter and modulation signal bispectrum analysis

Abstract: Transient impulses are important information for machinery fault diagnosis. However, the transient features contained in the vibration signals generated by planetary gearboxes are usually immersed by a large amount of background noise and harmonic components. Even mathematical morphology (MM) is an excellent anti-noise signal processing method that can directly extract the geometry of impulse features in the time domain, but the four basic operators of MM can only extract one-way impulses while cannot extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…However, FDC, FCD, FEO and FOE can only extract the one-sided spectrum of the signal. In order to be able to extract the two-sided spectrogram of the signal, Guo et al [21] proposed four enhanced morphological operators, their expressions are defined as follows:…”
Section: B Eavghmentioning
confidence: 99%
See 1 more Smart Citation
“…However, FDC, FCD, FEO and FOE can only extract the one-sided spectrum of the signal. In order to be able to extract the two-sided spectrogram of the signal, Guo et al [21] proposed four enhanced morphological operators, their expressions are defined as follows:…”
Section: B Eavghmentioning
confidence: 99%
“…In order to solve the above problems and restore the fault signal characteristics to the greatest extent. In this paper, a new enhanced top-hat transform operator (EAVGH) is proposed by combining EAVG operator [21] and BTH operator. EAVGH can not only maintain the integrity of the fault signal, but also has a better filtering effect.…”
Section: Introductionmentioning
confidence: 99%
“…With the above advantages, MSB has caused widespread concern in rotating machinery fault detection. [34][35][36][37][38] Zhang et al 34 put forward a new approach to detect gear wear using the MSB for timely prediction and maintenance. Tian et al 35 demonstrated that MSB-based method is capable of generating more robust diagnosis results for detecting common bearing faults in a series of representative scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous bispectrum-related research works are oriented on the analysis of the statistical relations between multiple narrowband spectral components, generated due to machinery nonlinearities, and, therefore, representing clear poly-harmonic spectral patterns. The bispectrum has been used for helicopter gear system fault detection [43], for AC motor current modulation estimation, for the analysis of vibration signals of spur gearboxes [44,45] and for planetary gear vibration diagnostics [46,47].…”
Section: Introductionmentioning
confidence: 99%